Dampak Hedonic Shopping Value dan Shopping Lifestyle pada Keputusan Pembelian Impulsif Pelanggan Shopee di Sidoarjo - Nadia Nur Lailatul R; Dina Amalia Khoirun Nadha R; Moch. Fahmi Syehfuddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Online shopping has become a rapidly growing trend among the Indonesian people. Shopee, as one of the popular online shopping platforms, was chosen as the focus of this research to analyze impulsive buying decisions. This study aims to investigate the influence of Hedonic Shopping Value and Shopping Lifestyle on the impulsive buying decisions of Shopee customers in Sidoarjo. This research uses a quantitative method, with data collection through questionnaires distributed to Shopee consumers in Sidoarjo and obtaining a sample of 75 respondents. The sampling technique used is nonprobability sampling. The data obtained were analyzed using Partial Least Square (PLS) with the help of the SmartPLS 4.0 application. The results show that Hedonic Shopping Value and Shopping Lifestyle have a significant influence on impulsive buying decisions.